INVESTIGATING EFL STUDENTS PERCEPTIONS OF PERPLEXITY AI FOR ARGUMENTATIVE WRITING - Milda Anggia; Wahid Hasim; Ateng Kurnia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The presence of Artificial Intelligence (AI) technologies such as Perplexity AI has transformed language learning, particularly in the way students access academic information quickly and interactively. This study aims to analyze English as a Foreign Language (EFL) students’ perceptions of the use of Perplexity AI in argumentative writing, particularly in terms of functionality, accessibility, and trust in the information sources generated by the platform. This study employed a descriptive qualitative approach, with data collected through questionnaires and interviews involving students who actively used Perplexity AI in academic writing activities. The data were analyzed through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of students’ experiences in utilizing the AI technology. The findings revealed that Perplexity AI helped students obtain references more quickly, facilitated the development of argumentative ideas, and improved the efficiency of the writing process. However, the study also identified concerns regarding the potential for technological dependency and the decline of critical thinking skills when AI is used without appropriate academic supervision. Therefore, the use of Perplexity AI in English language learning should be accompanied by pedagogical guidance and the strengthening of academic ethics so that the technology can be utilized critically, responsibly, and in ways that maintain the originality of students’ work. ABSTRAK Kehadiran kecerdasan buatan (Artificial Intelligence/AI) seperti Perplexity AI telah membawa perubahan dalam pembelajaran bahasa, khususnya dalam cara mahasiswa memperoleh informasi akademik secara cepat dan interaktif. Penelitian ini bertujuan untuk menganalisis persepsi mahasiswa Pendidikan Bahasa Inggris (EFL) terhadap penggunaan Perplexity AI dalam penyusunan tulisan argumentatif, terutama pada aspek fungsionalitas, kemudahan akses, dan tingkat kepercayaan terhadap sumber informasi yang dihasilkan. Penelitian menggunakan pendekatan deskriptif kualitatif dengan pengumpulan data melalui kuesioner dan wawancara terhadap mahasiswa yang aktif menggunakan Perplexity AI dalam kegiatan menulis akademik. Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan untuk memperoleh gambaran mengenai pengalaman mahasiswa dalam memanfaatkan teknologi AI tersebut. Hasil penelitian menunjukkan bahwa Perplexity AI membantu mahasiswa menemukan referensi secara lebih cepat, mempermudah pengembangan ide argumentatif, serta meningkatkan efisiensi proses penulisan. Namun, penelitian ini juga menemukan adanya kekhawatiran terkait potensi ketergantungan teknologi dan menurunnya kemampuan berpikir kritis apabila penggunaan AI tidak disertai kontrol akademik yang tepat. Dengan demikian, penggunaan Perplexity AI dalam pembelajaran bahasa Inggris perlu disertai arahan pedagogis dan penguatan etika akademik agar teknologi dapat dimanfaatkan secara kritis, bertanggung jawab, dan tetap mendukung orisinalitas karya mahasiswa.